Pioneering experiential integrated pre-school design archetype in Malaysia - Azmin, Aida Kesuma; Mahmood, Wan Akfan Ikhlan (Jabatan Seni Bina, Universiti Kebangsaan Malaysia, 2014)
Early childhood education plays an important role in developing assertive nation. In order to become a productive member of the nation, children should be nurtured to grow holistically and equipped with abilities, knowledge and skills. Physical environment is one of the crucial aspects in shaping children’s behaviour and development. At present, most pre-school designs in Malaysia are based on converted buildings or adaptive re-use schemes. Hence, the learning environments are not specially designed to cater for the specific needs of the children to develop healthily and positively. The study highlights the relevance of experiential architectural design approach to pre-school so as to facilitate emancipatory preschool design, with integrated “Education and Care” concept.